Abnormal Voxel-Based Degree Centrality in Patients With Postpartum Depression: A Resting-State Functional Magnetic Resonance Imaging Study - Zhang, Shufen; Li, Bo; Liu, Kai; Hou, Xiaoming; Zhang, Ping (Frontiers in Neuroscience, 2022)
Postpartum depression (PPD) is a major public health concern with significant consequences for mothers, their children and their families. However, little is known about its underlying neuropathological mechanisms. The voxel-based degree centrality (DC) analysis approach provides a new perspective for exploring the intrinsic dysconnectivity pattern of whole-brain functional networks of PPD. Twenty-nine patients with PPD and thirty healthy postpartum women were enrolled and received resting-state functional magnetic resonance imaging (fMRI) scans in the fourth week after delivery. DC image, clinical symptoms correlation and seed-based functional connectivity (FC) analyses were performed to reveal the abnormalities of whole brain functional network in PPD. Compared with healthy controls (HCs), patients with PPD exhibited significantly increased DC in the right hippocampus (HIP.R) and left inferior frontal orbital gyrus (ORBinf.L). The receiver operating characteristic (ROC) curve analysis showed the area under the curve (AUC) of the above two brain regions are all over 0.7. In the seed-based FC analyses, the PPD showed significantly decreased FC between the HIP.R and right middle frontal gyrus (MFG.R), between the HIP.R and left median cingulate and paracingulate gyri (DCG.L), and between the ORBinf.L and the left fusiform (FFG.L) compared to HCs. The PPD showed significantly increased FC between the ORBinf.L and the right superior frontal gyrus, medial (SFGmed.R) compared with HCs. Mean FC between the HIP.R and DCG.L positive correlated with EDPS scores in PPD group. This study provided evidences of aberrant DC and FC within brain regions in PPD patients, which were associated with the default mode network (DMN) and limbic system (LIN). Identification of these above altered brain areas may help physicians to better understand neural circuitry dysfunction in PPD.